Kolej Kediaman Tun Ahmad Zaidi homepage / Leong Wing Kin - Leong , Wing Kin (2000)
By the middle of 1990s, World Wide Web had transformed the online world tremendously. Users from all over the world were able to access and select varies types of information from the online world through the system at hypertext called homepage. Through homepage, there are hyperlinks that can link to all the other homepages thus enrich the interaction and developments of humans-to-humans communication on the Web by enabling users to distribute executable content electronically. Because of these reasons, the first Kolej Kediaman Tun Ahmad Zaidi (KKTAZ)'s homepage was created. The Kolej Kediaman Tun Ahmad Zaidi (KKTAZ)'s homepage was an attractive and interactive homepage that provide users with a high degree of selectivity over the information they want to view. The features of this homepage are structured mainly into sections namely; background, facilities, administrator, links, projects, student and alumni. The integration of advanced features such as the online chatting, discussion box, complaint and announcement box further enhanced the existing KKT AZ's homepage by allowing more sophisticated and interactive online tasks to be executed among students and the administrator. The development tools for this homepage are mainly Microsoft lnterdev 6.0, and using ASP technologies on Microsoft Window 98 Personal Web Server platform, utilizing Microsoft Access 97 database.